Design Study of Modular Lead-Bismuth Cooled Fast Reactors with Nitride Fuel - Abu Khalid Rivai; Zaki Su’ud; Ferhat Aziz (Institut Teknologi Bandung, 2003)
This paper discusses designs of modular lead-bismuth cooled fast reactors fueled with uranium nitride. The power range of the reactors under study was between 75 MWt and 700MWt. The reactors were designed by optimizing the use of natural uranium blanket and nitride fuel to prolong the fuel cycle. The fuels were enriched uranium nitride which can be used without refueling for 10 years. This study was done on pancake, balance and tall cylindrical types of cores. The results of calculation showed that the maximum excess reactivity in all core designs under study was 0.36 dollar. As for the burnup at EOC, the highest was in the 700 MWt balance core type with 11.95%, and the lowest was at 75MWt pancake core with 2.4% burnups. Capability of burnup in general was quite high. The maximum peak power density obtained was 324 W/cc, i.e. in 700 MWt tall type of core. The peak power densities of these reactores were well below those of the average fast reactors, which were indicative of good safety and controllability of operation.